Determination of anabolic steroid hormones in animal muscle tissues by gas chromatography/mass spectrometry - Chen, Jie; Qin, Yan; Zhang, Meijin (Sepu, 2006)
A gas chromatography/mass spectrometry (GC/MS) method was developed for the determination of multi-residues of steroid anabolic hormones epitestosterone (ETS), testosterone 17-propionate (PTS), nandrolone (17beta-NT), 17alpha-methyltestosterone (MTS), 17beta-estradiol (17beta-ES), estriol ( EST), 17alpha-ethinylestradiol (EES), estrone (ESN) and 17beta-estradiol 3-benzoate (BES) in the muscle tissues of various animal species. Homogenized tissue samples were enzymatically digested in acetate buffer (pH 5.0). Consequently, methanol was added and the mixtures were extracted under ultrasonication incubation. Clean-up was carried out for at least two times with methyl tert-butyl ether (MTBE) liquid-liquid partitioning followed by a reversed-phase solid phase extraction (SPE) cartridge purification. The eluate with methanol was evaporated to dryness by N2 at 40 degrees C and derivatization was achieved with N-methyl-N-( trimethylsilyl) trifluoroacetamide/iodotrimethylsilane/dithioerythritol (MSTFA-TMIS-DTE) at 60